Effect of packaging materials on the chemical composition and microbiological quality of edible mushroom (Pleurotus ostreatus) grown on cassava peels. Issue 4 (12th March 2015) - Ajayi, Oluwakemi; Obadina, Adewale; Idowu, Micheal; Adegunwa, Mojisola; Kajihausa, Olatundun; Sanni, Lateef; Asagbra, Yemisi; Ashiru, Bolanle; Tomlins, Keith
Abstract Edible fungi such as mushrooms are highly perishable and deteriorate few days after harvest due to its high moisture content and inability to maintain their physiological status. In this study, the effect of packaging materials on the nutritional composition of mushroom cultivated from cassava peels was investigated. Mushroom samples were dried at 50°C in a cabinet dryer for 8 h. The dried mushroom samples packaged in four different packaging materials; high density polyethylene (HDPE), polypropylene (PP), laminated aluminum foil (LAF), high density polyethylene under vacuum (HDPEV) were stored at freezing (0°C) temperatures for 12 weeks. Samples were collected at 2‐week intervals and analyzed for proximate composition (carbohydrate, protein, fat, fiber, ash, moisture), mineral content (calcium, potassium), vitamin C content, and microbiological qualities (total aerobic count, Pseudomonal count, Coliform count, Staphylococcal count, Salmonella count) using the standard laboratory procedures. Carbohydrate, protein, fat content of dried mushrooms packaged in HDPE at freezing temperature ranged from 45.2% to 53.5%, 18.0% to 20.3%, and 3.2% to 4.3%, while mushrooms in polypropylene ranged from 45.2% to 53.5%, 18.5% to 20.3%, 2.6% to 4.3%. Carbohydrate, protein, fat of mushroom in LAF ranged from 47.8% to 53.5%, 17.3% to 20.3%, and 3.3% to 4.3%, respectively, while carbohydrate, protein, fat of mushroom in HDPEV ranged from 51.1% to 53.5%, 19.5% to 20.3%, and 3.5% to 4.3%. Microbiological analysis showed that total aerobic count, Pseudomonal count, and Staphyloccocal count of dried mushroom ranged from 2.3 to 3.8 log cfu/g, 0.6 to 1.1 log cfu/g, and 0.4 to 0.5 log cfu/g, respectively. In conclusion, dried mushroom in HDPE packaged under vacuum at freezing temperature retained the nutritional constituents than those packaged with other packaging materials.